Kedudukan Penyidik Pegawai Negeri Sipil (PPNS) Keimigrasian dalam Penegakan Hukum Pidana Terhadap Imigran Ilegal - Dea Adzkia; Elwidarifa Marwenny (CV. ITTC INDONESIA, 2024)
Indonesia is one of the countries that adheres to a state system based on law, both in the exercise of government power and based on law. Civil Servant Investigators (PPNS) are certain officials or one of the state apparatus or state institutions who are given special authority by law to carry out investigations into criminal acts where in carrying out their duties and responsibilities they are under the Coordination and Supervision of Police Investigators (Korwas PPNS). The position of the Immigration PPNS is very important because matters relating to immigration are closely related to the sovereignty of the Indonesian state. Immigration PPNS investigators not only have to comply with Law No. 6 of 2011 concerning Immigration but also have to comply with the rules contained in Law no. 8 of 1981 concerning criminal procedural law and must also obey and obey other legal regulations in Indonesia. The discussions in this research are 1) the regulations and principles of criminal law enforcement implemented by Immigration PPNS related to supervision theory; and 2) the position of PPNS Immigration in enforcing criminal law against illegal immigrants. This research uses normative juridical with a case approach using secondary data in the form of related laws, books, journals, legal dictionaries and other related documents so that it can be concluded that the regulations and principles of Immigration PPNS are related to the theory of supervision. This has a huge responsibility and is very important for Indonesia's sovereignty because this can threaten the justice of Indonesian society and has the potential to cause social jealousy if illegal immigrants who enter Indonesian territory are not prosecuted and are not dealt with firmly. A real example in the field is the commotion that occurred in the community due to Rohingya refugees who were not dealt with firmly and seemed to be left to their own devices.